Study on the molecular mechanism of nightshade in the treatment of colon cancer. Issue 1 (1st January 2022) - Na, Song; Ying, Li; Jun, Cheng; Ya, Xiong; Suifeng, Zhang; Yuxi, He; Jing, Wang; Zonglang, Lai; Xiaojun, Yang; Yue, Wu
ABSTRACT: The present study attempts to explore the effective components, action targets, and potential mechanism of nightshade for colon cancer treatment. The relationship network diagram of 'traditional Chinese medicine – component – target – disease' was firstly constructed by employing network pharmacology. Experiments were conducted in vivo and in vitro to verify the influence of quercetin, the core effective component of nightshade, on colon cancer. Meanwhile, the regulatory effects of quercetin on core targets and main signaling pathways were determined. Based on the network diagram of 'traditional Chinese medicine – component – target – disease' and KEGG analysis, quercetin might exhibit certain effects on colon cancer treatment by regulating the biological behavior of core targets related to cell apoptosis in tumors including PIK3R1, PIK3CA, Akt1, and Akt2. Furthermore, quercetin has been demonstrated in vitro experiments to suppress the proliferation and migration of colon cancer cells whereas promote their apoptosis in a dose-dependent fashion. In vivo experiments indicate that quercetin had an antitumor effect on human colon cancer SW480 cells in nude mice bearing tumors. Furthermore, PIK3CA could bind to quercetin directly, which is validated by immunocoprecipitation. Therefore, the activation of PI3K/AKT phosphorylation was inhibited by quercetin and moreover the expressions of apoptotic proteins caspase-3 and Bcl2-Associated X protein (BAX) were up-regulated. In conclusion, the potential mechanism of nightshade lies in the activation of the PI3K/AKT signaling pathway inhibited by quercetin, thus promoting apoptosis of colon cancer cells for colon cancer treatment. Graphical Abstract: uf0001